DHL and facilitating small business trade - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
This case study tracks the growth of DHL, from a small courier between California and Hawaii, to an international shipping organization. In more recent years, DHL has directed focus to facilitating trade for small and medium businesses in emerging markets, and this case investigates the various strategies by which these markets are reached.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). DHL and Facilitating Small Business Trade. In International marketing (p. 111). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; DHL Express (Firm); Express service -- Case studies